Prognostic Factors for Return to Sport After High Tibial Osteotomy: A Directed Acyclic Graph Approach. Issue 8 (July 2019) - Hoorntje, Alexander; Kuijer, P. Paul F.M.; van Ginneken, Berbke T.; Koenraadt, Koen L.M.; van Geenen, Rutger C.I.; Kerkhoffs, Gino M.M.J.; van Heerwaarden, Ronald J.
Background: High tibial osteotomy (HTO) is increasingly used in young and physically active patients with knee osteoarthritis. These patients have high expectations, including return to sport (RTS). By retaining native knee structures, a return to highly knee-demanding activities seems possible. However, evidence on patient-related outcomes, including RTS, is sparse. Also, time to RTS has never been described. Furthermore, prognostic factors for RTS after HTO have never been investigated. These data may further justify HTO as a surgical alternative to knee arthroplasty. Purpose: To investigate the extent and timing of RTS after HTO in the largest cohort investigated for RTS to date and to identify prognostic factors for successful RTS. Study Design: Case-control study; Level of evidence, 3. Methods: Consecutive patients with HTO, operated on between 2012 and 2015, received a questionnaire. First, pre- and postoperative sports participation questions were asked. Also, time to RTS, sports level and frequency, impact level, the presymptomatic and postoperative Tegner activity score (1-10; higher is more active), and the postoperative Lysholm score (0-100; higher is better) were collected. Finally, prognostic factors for RTS were analyzed using a logistic regression model. Covariates were selected based on univariate analysis and a directed acyclic graph. Results: We included 340 eligible patients of whom 294 sufficiently completed the questionnaire. The mean follow-up was 3.7 years (± 1.0 years). Out of 256 patients participating in sports preoperatively, 210 patients (82%) returned to sport postoperatively, of whom 158 (75%) returned within 6 months. We observed a shift to participation in lower-impact activities, although 44% of reported sports activities at final follow-up were intermediate- or high-impact sports. The median Tegner score decreased from 5.0 (interquartile range [IQR], 4.0-6.0) presymptomatically to 4.0 (IQR, 3.0-4.0) at follow-up ( P < .001). The mean Lysholm score at follow-up was 68 (SD, ± 22). No significant differences were found between patients with varus or valgus osteoarthritis. The strongest prognostic factor for RTS was continued sports participation in the year before surgery (odds ratio, 2.81; 95% CI, 1.37-5.76). Conclusion: More than 8 of 10 patients returned to sport after HTO. Continued preoperative sports participation was associated with a successful RTS. Future studies need to identify additional prognostic factors.